Delay Factors of Construction Projects in Oman - Al Amri, Amur Ali Mussallam; Oztemir, Ali Erhan (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The construction industry is the second largest economic sector of the Sultanate of Oman. The construction industry plays important role in infrastructural development both for the public and private sectors. The delays in construction projects impact directly the economic development of the country. The present study aimed to analyze the delays in a construction project by conducting a survey based on a questionnaire. The questionnaire survey is answered by 74 respondents and the quantitative data is further subjected to statistical analysis. The results are further tested through the Pearson chi-square test of independence and Cramer’s V tests. The results show that several factors contribute to the project delays in Oman including cultural differences, design changes, poor project management, and changes in project scope at the time of project execution. The managerial issues involved payment delays to contractors and authoritarian delays. The clients faced poor planning and execution of the project by the contractor and sub-contracting of the critical project phases.